Public spending on climate change in Africa: Experiences from Ethiopia, Ghana, Tanzania and Uganda - Neil Bird; Felix Ankomah Asante; Simon Bawakyillenuo; Nella Canales Trujillo; Zwedu Eshetu; Godber Tumushabe; Pius Yanda; Marigold Norman; Cynthia Addoquaye Tagoe; Aklilu Amsalu Taye; Nicholas Ashiabi; Deograsias Mushi; et al. (Overseas Development Institute (ODI), 2016)
Public spending on climate change in Africa describes the extent to which public expenditure responds to national climate change policy and the institutional demands required to implement such policy. The four countries of the study - Ethiopia, Ghana, Tanzania and Uganda - provide insights into the early mobilisation of climate change finance, as each country attempts to address the new challenges that climate change is bringing about. The report is divided into three parts. The first part introduces the concept of climate change finance and outlines the effectiveness framework used in each of the country studies. The methodological challenges associated with public expenditure reviews as applied to national climate change actions are also described. The second part provides in-depth country accounts for Ethiopia, Ghana, Tanzania and Uganda, on the level and nature of climate change-relevant public spending, set in the context of each country's macroeconomic and public finance management systems. The final section concludes by drawing lessons for climate change policy development, institutional strengthening, local delivery of climate change finance and the monitoring of public finance, based on the insights gained from the country studies.
Keywords: 330